2018
DOI: 10.1590/1413-81232018239.02532018
|View full text |Cite
|
Sign up to set email alerts
|

Saúde bucal de adolescentes rurais quilombolas e não quilombolas: um estudo dos hábitos de higiene e fatores associados

Abstract: Resumo Este estudo avaliou os hábitos de higiene bucal e sua associação com fatores socioculturais, ambientais e relacionados à utilização de serviços odontológicos entre adolescentes rurais quilombolas e não quilombolas do interior da Bahia. Foi um estudo transversal realizado em 2015. Estimaram-se prevalências e razões de prevalências para os desfechos e foi conduzida análise múltipla por regressão de Poisson com variância robusta. Foram entrevistados 390 adolescentes, 42,8% quilombolas. Escovação dentária i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
9
0
6
Order By: Relevance
“…Difficulty eating was the impact most frequently reported by rural adolescents, as found in many other studies [2,7,25,26]. Importantly, around 20% of the adolescents interviewed reported toothache in the past 6 months [11]. Therefore, it is reasonable to assume that the most prevalent negative impact is physical rather than psychological in nature [2].…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Difficulty eating was the impact most frequently reported by rural adolescents, as found in many other studies [2,7,25,26]. Importantly, around 20% of the adolescents interviewed reported toothache in the past 6 months [11]. Therefore, it is reasonable to assume that the most prevalent negative impact is physical rather than psychological in nature [2].…”
Section: Discussionmentioning
confidence: 51%
“…A previous study found that the two populations did not differ significantly as regards to other aspects related to oral health conditions, including toothache, oral health self-assessment, and need for dental treatment. However, differences in the use of dental services were found [11]. Therefore, given that quilombola adolescents had a lower prevalence of dental consultations at some point in their lives, and that tooth brushing is a technique that must be taught [27], it is acceptable to assume that different oral hygiene techniques can influence tooth brushing discomfort, as well as other oral clinical conditions not yet investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As own survey shows, only 38.15% of the 17-year-old youths use mouthwashes in oral care, and no statistically significant difference was found between the genders. Silva et al [3] in their own studies stated that approximately 75% of the youths aged 10-19 years evaluated their oral cavity condition as very good, emphasizing that the reason for that is the use of various methods of maintaining good oral health, including mouthwashes.…”
Section: Disscussionmentioning
confidence: 99%